Pengembangan Modul IPA Terpadu Berbasis Problem Based Learning Materi Gerak Untuk Meningkatkan Kemampuan Berfikir Kritis Siswa Kelas VIII-P MTSN 4 Jombang - Huda, Hisbulloh (Multidisciplinary Journal of Education , Economic and Culture, 2024)
The research aims to determine the feasibility of a PBL-based integrated science module on the theme of Movement developed and the effectiveness of the developed module in improving students' critical thinking skills. The method applied is Research and Development (R&D). Product trials were carried out at MTsN 4 Jombang, East Java. The research results show that the assessment of the PBL-based integrated science module by experts obtained an average score of 3.6 with appropriate criteria. In small-scale trials, the module developed received an average percentage score of 82% with very good responses from students. The results of large-scale trials show that the module developed in learning activities received an average percentage score of 88.96% from students and teachers 94.79% with very good responses from teachers and students. The effectiveness of the module in improving students' critical thinking skills obtained an average -average score 0.6 with medium criteria. Student learning outcomes obtained an average score of 80.34 with classical class completeness of 100%. Based on the research results, it can be concluded that the PBL-based integrated science module with Motion material is feasible and effective in the learning process for class VIII-P MTsN 4 Jombang, East Java